The Thai Internalized HIV-related Stigma Scale - Uthis, Penpaktr; Suktrakul, Sunisa; Wiwatwongwana, Rangsima; Tangmunkongvorakul, Arunrat; Sripan, Patumrat; Srithanaviboonchai, Kriengkrai (Frontiers in Psychology, 2023)
Introduction Internalized stigma among people living with HIV has been linked to a range of negative consequences. The current study describes the development and validation of a contextually appropriate internalized HIV-related Stigma Scale for people living with HIV in Thailand. Methods The study was carried out in two stages from 2018 to 2019: developing items based on the findings of focus group discussions and pilot testing the original list of items and validating the instrument. In the cross-sectional survey stage, a sample of 400 people living with HIV was used to validate the test items in accordance with their psychometric characteristics. Results The study’s outcome was the 22-item Thai Internalized HIV-related Stigma Scale (Thai-IHSS). The exploratory factor analysis showed that the Thai-IHSS consisted of four components: negative thoughts toward self (5 items), anticipated negative thoughts (7 items), effects of negative thought toward self (6 items), and effects of negative thoughts toward family and access to healthcare services (4 items). Discussion The Thai-IHSS had acceptable concurrent, convergent, and congruent validity according to the findings. Additionally, the 8-item Thai-IHSS brief, which included two items for each component, was detailed. The Thai-IHSS is valid and reliable for use in Thailand and other countries with comparable sociocultural environments.